Visfatin Immunoreactivity in Rat Brain Tissues of Experimental Ischemia-Reperfusion - Balgetir, Ferhat; Ozturk, Sait; Yalcin, Alper (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY